2020
DOI: 10.3892/ol.2020.11641
|View full text |Cite
|
Sign up to set email alerts
|

ALOX12B promotes carcinogenesis in cervical cancer by regulating the PI3K/ERK1 signaling pathway

Abstract: Cervical cancer is a malignant disease and a threat to women's health worldwide. Surgical resection followed by radiotherapy or chemotherapy is the main treatment strategy for cervical cancer; however, patients with cervical cancer, especially those with late-stage disease, may not benefit from these traditional therapies, which results in poor clinical outcome. ALOX12B is a gene encoding lipoxygenase, and a mutation in ALOX12B was detected in lung and breast cancer. Furthermore, ALOX12B is essential to the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…ALOX12B, R-type of ALOX12 catalyzed by ALOX12, is necessary for p53-mediated antitumor effect via ferroptosis ( Mashima and Okuyama, 2015 ). Jiang et al (2020) have demonstrated that ALOX12B promotes cervical cancer progression through modulating the PI3K/ERK1 signaling pathway. ALOX12B has a negative relation to the prognosis of LUAD in our study, which indicates that ALOX12B may be involved in some other tumor regulatory mechanisms ( Jiang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…ALOX12B, R-type of ALOX12 catalyzed by ALOX12, is necessary for p53-mediated antitumor effect via ferroptosis ( Mashima and Okuyama, 2015 ). Jiang et al (2020) have demonstrated that ALOX12B promotes cervical cancer progression through modulating the PI3K/ERK1 signaling pathway. ALOX12B has a negative relation to the prognosis of LUAD in our study, which indicates that ALOX12B may be involved in some other tumor regulatory mechanisms ( Jiang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…ALOX12B protein, another isoform of arachidonic acid 12-lipoxygenase, mainly catalyzes arachidonic acid to 12R-hydroxyeicosatetraenoic acid ( Zheng et al, 2011 ). Jiang et al revealed that the inhibition of ALOX12B could restrain cervical cancer cell proliferation and growth through suppressing the PI3K/ERK1 pathway, suggesting that it can be taken as a good biomarker to provide new therapeutic strategies for cervical cancer patients ( Jiang et al, 2020 ). In addition, Chu et al reported that ALOX12 could oxygenate polyunsaturated fatty acids, which in turn induce p53-mediated tumor cell ferroptosis ( Chu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Low expression levels of ALOX12B were found to significantly reduce both cell proliferation and clone formation ability, and block cell cycle at G1 phase in cervical cancer. Tumor growth was also suppressed in vivo in a xenograft tumor model (33). Studies associating PACSIN1 have revealed that it works as a critical regulator of synaptic inhibition (30), regulator for tolllike receptor (TLR)7/9 interferon response (34), for axonal elongation and branching (35), and α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPA) receptor trafficking (36).…”
Section: Discussionmentioning
confidence: 99%